Forage Groups - Loiola Edvan, Ricardo; Mauro Santos, Edson (IntechOpen, 2019)
The correct use of forage as animal food is a less expensive way of improving animal performance and reducing the costs of animal products. Therefore, we hope the book Forage Groups allows its readers to acquire knowledge about cultivation, harvesting, and conservation of grass and legumes. This book presents data from many countries around the world and we hope it will be useful for all interested readers in improving their background in forage.